The Immunologic Role of Vitamins C and D and Their Potential in the Management of COVID-19 Infections - Antoine-Frank, Chrystal D.; Seyni Boureima, Rimanatou; Ellis, Kaydeonne T.; R. Antoine, Malcolm (Jr); Shrestha, Merina (International Journal of Innovative Research in Medical Science, 2021)
The Severe Acute Respiratory Syndrome Coronavirus 2 causes COVID-19 infection. Vitamins C and D have been investigated for their effects on COVID-19 including the severity of it’s symptoms and complications. These vitamins may provide some benefits against the Severe Acute Respiratory Syndrome Coronavirus 2 as they modulate the immune system in addition to having anti-viral effects. This review will investigate the effects of vitamins C and D on COVID-19 infection to determine their benefits in the management of patients infected by the Severe Acute Respiratory Syndrome Coronavirus 2.